The Relationship Between Inflammatory Cytokines and Calciotropic Hormones in South Asian and Caucasian Men. (29th May 2020) - Altasan, Asma; Cheung, May; DeLuccia, Rosemary; Parekh, Rushali; Al-Ani, Sumer; Sukumar, Deeptha
Abstract: Objectives: The study objective was to identify the differences in inflammatory profile, and possible predictors of vitamin D and parathyroid hormone (PTH) concentrations between South Asian Indians (SAIs) and Caucasians. Methods: Healthy SAIs and Caucasian men, who were 22 to 50 years of age, were recruited. Anthropometric measurements including body composition using Dual X-Ray Energy Absorptiometry and serum 25 hydroxy-vitamin D (25(OH)D), PTH, Matrix metallopeptidase 9 (MMP-9), C-terminal peptide (CTX), osteocalcin, insulin, adiponectin, and serum glucose concentrations were obtained. Independent t-test was used to report the mean differences between groups. Spearman correlation, and linear regression were used to identify possible predictors of 25(OH)D, and PTH levels. A P -value of less than 0.05 was considered significant. Results: 28 SAIs and 28 Caucasians completed the study. Both groups did not significantly differ in their age and BMI. The mean 25(OH)D levels were 22.3 ± 6.6 ng/mL and 31.96 ± 9 ng/mL for SAIs and Caucasians, ( P < 0.01). The mean PTH levels were 65.0 ± 26.7pg/mL, and 53.5 ± 30.1pg/mL for SAIs and Caucasians, ( P > 0.05). The mean adiponectin levels were significantly lower among SAIs (2.26 ± 1.8 ng/mL) compared to the Caucasians (71 ± 2.4 ng/mL), ( P < 0.001). The MMP-9 levels were significantly higher in the Caucasians ( P = 0.050). The regression analysis found both serum 25(OH)D and insulin concentrations as best predictors of PTH levels in SAIs, while MMP-9 level was the best predictor of PTH levels in Caucasians. Serum glucose and PTH levels were best predictors of 25(OH)D levels in SAIs, while adiponectin level was the best predictor of the 25(OH)D in Caucasians. Conclusions: The differences in serum levels of 25(OH)D, MMP-9, and adiponectin between the two ethnic groups could explain why SAIs have a higher risk for chronic diseases. Future studies should consider improving vitamin D and adiponectin levels among SAIs via vitamin or minerals supplements that could improve their cardiometabolic health. Funding Sources: Drexel University.